The relationship between familial aid and number of children of married couples in Brgy. Malagyan, Miag-ao, Iloilo - Fagutao, Marie Nez May F.
This is a study on the relationship between familial aid and number of children of married couples. This study aims to describe the socio-demographic characteristics of married couples. It also aims to describe the nature of financial aid and goods received by married couples from their parents and siblings. Moreover, it aims to find out if there is a relationship financial aid received by married couples from their parents and siblings and their number of children. Also, the study aims to find out if there is a relationship between goods received by married couples from their parents and siblings and their number of children. Lastly, it aims to find out if there is a relationship between familial aid received by married couples from their parents and siblings and their number of children. The study involves 56 married couples of Barangay Malagyan, Miagao. They were chosen through random sampling method using the fishbowl technique. The interview schedule was the primary tool used to get the data needed for the study. The analysis of the study was based on frequency counts, percentages, and chi-square test for independence. The study revealed that majority of the couples were married for 6 to 10 years and have few children. Most of the husbands are between 33 and 37 years old, engages in service-oriented jobs, do not have secondary occupation, and only reached high school level. On the other hand, most of the wives are between 28 and 38 years old, reached high school level, and engaged in housekeeping and animal raising. Majority of the couples who received familial aid borrow money and received clothes from their parents and siblings. Furthermore, the study revealed that there is no relationship between financial aid received by married couples from their parents and siblings and their number of children. Also, there is no relationship between goods received by married couples from their parents and siblings and their number of children. Finally, there is no relationship between familial aid received by married couple from their parents and siblings and their number of children.